Does China control arctic mineral raw materials? How much, what, how and why? - Patrik Andersson; Per Kalvig (Danish Institute for International Studies (DIIS), 2022)
In this working paper, we explore these questions based on analysis of a dataset of mining and mineral exploration projects covering all the major commodities or commodity groups in six Arctic countries or territories - Canada, Greenland, Finland, Sweden, Norway and Alaska. We do so through an approach that moves beyond ownership of mines as a measurement of control. Mine ownership in itself has little significance for where the raw materials go to be processed. Industry demand and supply security hinge more on highly processed materials and advanced products than bulk raw materials. Our approach is instead to assess Chinese control over mineral flows from the Arctic using a comprehensive set of 'control parameters'. Compared to an ownership-based approach, we begin one step further upstream in the supply chain - at mineral exploration - and look one step further downstream, by taking into account control via, for example, offtake agreements or monopoly over processing technology. We find that Chinese companies are involved in a very small share of Arctic projects overall, that their activities cover a very wide range of commodities, most of which are focused on exploration, and that they are heavily concentrated in Canada. The scale of Chinese involvement might, however, be more extensive than our data shows because many Western miners view Chinese companies as their natural - and first choice - offtake partners. It is thus likely that many companies expect to sell to China but have not entered into a formal offtake agreement, or that we have just not been able to find evidence of such agreements. Our findings also suggest that while Chinese engagement in the Arctic mineral sector has been limited, the investments that have been made appear to support China's mineral strategy relatively well. This is evident from both the range of commodities that are targeted and from variations in degree of control across commodities that are differently prioritised in China's mineral strategy.
Keywords: 330; Natural resources and environment; Oil; gas and minerals; Defence and security; Defence and security policy; Foreign policy; Danish and European foreign policies; The politics of great and emerging powers